Pile design using eurocode 7 - Wong, Kia Fu (2014)
Singapore is converting the national building code from British Standards to Eurocode. The conversion will start in 2013 and after two years of transition, on 1 April 2015, Eurocode will be fully in force and British Standards withdrawn. The new code which is very much open to interpretation and did not specify exact calculation steps would cause difficulties to the designer to pick up the necessary design skills.